ダイ44ジ ナンキョク チイキ カンソク ニ オケル ナンキョクカイ カイヨウ カンソク ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 小達, 恒夫; オダテ, ツネオ; 福地, 光男; フクチ, ミツオ; Odate, Tsuneo; Fukuchi, Mituo (2002)
P(論文) 「第44次南極地域観測における南極海海洋観測に関する研究小集会」を, 2002年1月11日, 国立極地研究所講義室において開催した。参加者は11名であった。始めに, 2001年度の時系列観測の現況が報告された。第44次南極地域観測隊(JARE-44)における観測計画を議論した。現在のところ, 「専用観測船」には, JARE-44観測隊員3名が乗船し, 「南極地域観測第VI期5か年計画」に関わる観測実施項目を行い, 関連する研究項目として「南極海と地球環境に関する総合的研究」の一部が同行者によって実施される予定である。ケルゲレン海台を含むB海域での時系列観測は, 物理関係の観測が中心となる。「しらせ」, 「オーロラ・オーストラリス号」, 「海鷹丸」により, 時系列観測が可能となる。生物系観測の時系列観測は, 南緯60度以南, 東経140度線上のC海域で重点的観測を行うことで合意が得られた。 A workshop on "Oceanographic Studies in the Antarctic Ocean by the 44th Japanese Antarctic Research Expedition (JARE-44)" was held on January 11,2002,at the National Institute of Polar Research with 11 participants. At the beginning of the workshop, the present status of the time serial observation in 2001/02 austral summer was reported. In this workshop, the scientific plan for the time serial observation in 2002/03 was discussed. Three expeditioners of JARE-44 will participate in the field observation using a chartered vessel in order to investigate the science theme of the 6th phase of JARE. Part of the scientific theme, "Studies of the Antarctic Ocean and Global Environment" will be done by participants other than JARE-44 members. Physical oceanographic time serial studies will be focused on Target Area B, which includes the Keruguelen Plateau, by icebreaker Shirase, RMV Aurora Australis, and T/S Umitaka Maru. Biological oceanographic time serial studies will be conducted in Target Area C (>60°S, 140°E), by RMV Aurora Australis, T/S Umitaka Maru, the chartered research vessel, and icebreaker Shirase. departmental bulletin paper